Cu–Organic framework-derived V-doped carbon nanostructures for organic dye removal. Issue 48 (3rd December 2021) - Zhang, Xiao-Sa; Zhao, Hong-Tian; Liu, Yu; Li, Wen-Ze; Yang, Ai-Ai; Luan, Jian
Abstract : In this study, a novel MOF has been constructed as a precursor for the preparation of carbon nanostructures. Moreover, we have used V metal as a doping agent to boost the adsorption and photodegradation activity of the MOF-derived carbon nanostructures. Abstract : Metal–organic frameworks (MOFs) have recently emerged as a type of uniformly and periodically atom-distributed precursor and efficient self-sacrificial template to fabricate hierarchical porous-carbon-related nanostructured functional materials. In this work, we used Cu(ii ) ions and aromatic dicarboxylic acid to construct [Cu3 (4, 4′-oba)2 (μ2 -OH)2 (H2 O)2 ] n (4, 4′-H2 oba = 4, 4′-oxybisbenzoic acid) as a precursor for the preparation of carbon nanostructures. Doping foreign elements into intrinsic MOF-based nanomaterials is an effective way to enhance the adsorption property and photocatalytic activity; thus, we designed a facile method to synthesize a vanadium-doped mixture of Cu2 O and Cu nanoparticles encapsulated in a Cu-MOF-derived carbon nanostructure (C-V-1 ) in this work for the first time. Benefiting from the protection of the carbon shell and regulation of the electronic structure by doping vanadium and phase-mixing Cu2 O and Cu, the adsorption capacities of C-V-1 for MB, RhB, MO, CR and GV at room temperature are 174.13, 147.06, 179.92, 275.90 and 611.81 mg g −1 in 240 min, respectively, while the photocatalytic degradation rates are 88.14% for MB, 79.80% for RhB, 71.31% for MO, and 71.19% for CR after 4 h. In addition, the degradation rate is larger than 99.01% for GV after only 30 min of UV irradiation. This strategy of using a diverse MOF as a structural and compositional material to create a multifunctional composite/hybrid may expand the opportunities to explore highly efficient, fast and robust adsorbents and photocatalysts for water treatment.